Asteroschema sampadae (Ophiuroidea: Asteroschematinae), a new deep-sea brittle star from the continental slope off the southern tip of India - Parameswaran, Usha V.; U., Abdul Jaleel K. (Zootaxa, 2012)
A new species of deep-sea euryalid ophiuroid, Asteroschema sampadae is described from the continental margin off thesouthern tip of India. This species is distinguished from others in having scattered, distinctly conical epidermal ossiclesthroughout the aboral surface of the disc and arms and minute, scattered granular ossicles on the oral side. This is the fourthreport of the genus Asteroschema from Indian waters (including Andaman & Nicobar Islands) and the first report of thisgenus from around the Indian peninsula since the report of Asteroschema flosculus from a coral bank off Nellore, Andhra Pradesh by Alcock in 1893.